Bad forum shopping and judicial review: “causa causae est causa causati” (STS de 25 de Noviembre de 2019) decision of the Supreme Court of November 25, 2019 - Juárez Pérez, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This judgement by the Supreme Court resolves an application for review of sentence based on the ground for opposition referred to in Article 510.4º of the Code of Civil Procedure (CCP): an unfair judgement caused by malicious conduct. The plaintiff intentionally concealed and distorted the information about defendant’s domicile; as a result, the judgment was given by default. The Court did not examine the substantive matter and declares the expiration of the review action, because more than three months had passed since the fraud was discovered (Art. 512 CCP). Before the procedure in Spain an identical process was taking place in New Jersey (USA). The question that arises is how a second process could be opened in Spain while the first was pending. The answer lies in a well-known institution of Private International Law: forum shopping.